Computer-related visual symptoms in office workers - Portello, Joan K; Rosenfield, Mark; Bababekova, Yuliya; Estrada, Jorge M; Leon, Alejandro (Ophthalmic & physiological optics, 2012)
Citation information: Portello JK, Rosenfield M, Bababekova Y, Estrada JM & Leon A. Computer‐related visual symptoms in office workers. Ophthalmic Physiol Opt 2012, 32, 375–382. doi: 10.1111/j.1475‐1313.2012.00925.x Purpose:  Many individuals report visual symptoms during office work and specifically computer use. This study determined the prevalence of symptoms in a population of office workers, and examined the association between these symptoms and both dry eye disease and other demographic factors. Method:  A written questionnaire was used to quantify the prevalence of symptoms in 520 New York City office workers, and to determine the effect of risk factors including gender, ethnicity, age, smoking, type of refractive correction and hours spent doing computer work. The questionnaire also examined the prevalence of ocular surface disease. Results:  A significant positive correlation was observed between the symptom score and the number of hours spent working on a computer in a typical day. The most prevalent symptom was tired eyes, which was reported by approximately 40% of subjects as occurring ‘at least half the time’. 32% and 31% of subjects reported symptoms of dry eye and eye discomfort, respectively. Symptoms varied significantly with gender (being greater in females), ethnicity (being greater in Hispanics) and the use of rewetting drops. A significant positive correlation was observed between computer‐related visual symptoms and the Ocular Surface Disease Index (OSDI), a measure of dry eye. Conclusions:  Visual symptoms associated with computer use occur frequently in the general population producing discomfort for extended periods of time. They are strongly associated with ocular surface disease. Therapeutic regimens need to be developed for this widespread condition.